Assessment of the Bacterial Content of Commercially Available Probiotic Products Containing Lactic Acid Bacteria and Their Probiotic Potentials in Jos - Florence Yachim Danjuma; Michael Macvren Dashen; Anayochukwu Chibuike Ngene; Otumala John Egbere (Advanced Gut & Microbiome Research)
Probiotic products containing lactic acid bacteria (LAB) are widely promoted for their health benefits, including support for vaginal and gastrointestinal health. However, concerns have emerged regarding the accuracy of product labeling and the viability of the claimed bacterial strains. This study is aimed at evaluating the microbial quality and probiotic potential of three commercial probiotic products marketed for vaginal health. LAB counts were determined, and isolates were identified based on standard microbiological methods. Probiotic properties were evaluated by testing tolerance to acidic pH, bile salts, phenol, and various temperatures, as well as antibacterial activity against selected pathogens. Results showed a significant discrepancy between labeled claim and actual viable counts. Product A retained only 0.96% of its labeled claim; Product B retained 0.12%, while Product C had no viable LAB. Strains isolated from Products A and B included Lactobacillus acidophilus, Lactobacillus plantarum, Lactobacillus rhamnosus, Bifidobacterium lactis, and Bifidobacterium bifidum. These isolates demonstrated varying degrees of acid, bile, and phenol tolerance, and several showed strong antagonistic activity against Staphylococcus aureus, Escherichia coli, and Klebsiella pneumoniae. All isolates were resistant to cloxacillin, ceftriaxone, and ceftazidime but remained sensitive to ciprofloxacin and levofloxacin. The use of CLSI standards, while offering methodological consistency, has limitations for nonclinical strains and should be interpreted cautiously. In conclusion, only two of the three evaluated probiotic products contained viable and functionally relevant LAB strains, raising concerns about quality assurance in commercial probiotics. The results highlight the need for stricter regulatory oversight and routine postmarket validation of probiotic formulations. A limitation of this study is the exclusive use of culture-based methods, which may not detect nonculturable but viable organisms. Future studies should incorporate molecular techniques for a more comprehensive microbial assessment and to verify the presence of transferable antibiotic resistance genes.